Effects of Resveratrol on Liver Function Tests in Patients with Non-Alcoholic Fatty Liver Disease: a Systematic Review and Meta-Analysis of Randomized Controlled Trials - P. Ebrahimpour; M. Karamian; A. Sharifi (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2024)
Background. Some studies have shown that resveratrol may prevent, delay, or treat liver damage. This study aimed to provide up-to-date evidence regarding the effect of resveratrol on the liver enzymes (ALT & AST) in NAFLD patients. We conducted a systematic review and meta-analysis to evaluate the effect of resveratrol on liver enzymes in patients with NAFLD by searching various databases for published RCTs.Methods. A systematic search in PubMed, Scopus, and Web of Science was performed up to September 2023. This systematic review and meta-analysis included all the RCT studies assessing resveratrol supplements on serum AST and/or ALT in NAFLD patients. The effect was presented as a mean difference and 95 % confidence interval (CI) in a random-effects model.Results. Finally, six eligible randomized controlled trials consisting of 256 patients were found. Resveratrol had no significant effect on serum ALT (Mean diff = 3.30 IU/L; 95 % CI: –2.34, 8.94; p = 0.25) and AST (Mean diff = 0.07 IU/L; 95 % CI: –2.96, 3.10; p = 0.96) concentrations. Moreover, subgroup analysis revealed that neither resveratrol dose nor intervention duration had any significant effect on the serum ALT and AST levels.Conclusion. The current evidence shows that resveratrol supplementation did not affect liver enzymes in NAFLD patients.